The Task of Machine Tool Operators in Small and Medium Enterprises in Indonesia - Bernardus Sentot Wijanarka; Nuchron Nuchron; Dwi Rahdiyanta; Theopile Habanabakize (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
The needs of operators for each type of industry are different because the type and the complexity of the task is different. Small and medium-sized industries require machine operators with better capabilities than operators in large companies, thus it is necessary to identify what tasks are performed by these operators. This study aim at (1) identifying duties of machine tool operators in small and medium enterprises, and (2) identifying tasks carried out by machine tool operators in small and medium enterprises. This study used a descriptive research method. The participants were eight machine tool operators from five small and medium enterprises in Yogyakarta, Indonesia. The data collection used document review, observation, questionnaires and focus group discussions. The data were analysed using descriptive analysis. The results of the study were (1) five duties done by machine tool operators are identified (maintaining safe work environment, maintaining the machine tools, analyzing the blueprint, performing machining operations, cleaning the machines and the workplace), and (2) twenty seven tasks executed by machine tool operators are identified; twenty-two knowledge and skills, seventeen behaviors, and eighteen machines, tools and equipment required by machine operators.